An investigation to the Effect of Copper Addition on the Characteristics of Ni-Ti Shape Memory Alloy - Rahman, Mohammed; Takhakh, Ayad M. (Nahrain University College of Engineering Journal, 2017)
The effect of Cu addition on the physical and mechanical properties of Nickel-Titanium (weight percentage ) shape memory alloy were investigated , density , porosity , compression strength ,Shape Effect (strain recovery), ,micro-hardness , Conducted to estimate the Cu effect ,a Different amount of Cu (2%,5%,10% ) weight percent were added with different compactingPressure (450MPa and 600MPa). Significant effect on master alloys properties especially the alloys that have 5%Cu and 10%Cu has been observed.